Innovation of the LIRACLE Model: Case of Gajah Wong River Pollution by Pb Metal - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
Gajah Wong River is one of the rivers in Yogyakarta. Gajah Wong River is an aquatic ecosystem whose existence is greatly influenced by activities or activities around it or in the river basin. Several human activities cause pollution in this river. One of the pollutants found is Pb metal. Students, as a quality young generation, must be able to find alternative solutions to this problem. Literacy and Research-Oriented Cooperative Problem-Based Learning (LIRACLE) is a new learning model developed for learning in higher education. In its development, LIRACLE is used to develop chemical literacy skills, get used to scientific thinking, and develop the science process skills of prospective chemistry teachers. The purpose of this study is to describe the application of the LIRACLE model in the case of pollution of the Gajah Wong River by Pb metal. The description includes observations of the implementation of each syntax of LIRACLE. The number of water samples used in this study was taken from one point on the Gajah Wong River. The chemical concept studied is adsorption, the theory of which has been studied in the